2019
DOI: 10.1002/fld.4786
|View full text |Cite
|
Sign up to set email alerts
|

A face‐based monolithic approach for the incompressible magnetohydrodynamics equations

Abstract: Summary A novel numerical algorithm has been developed to solve the incompressible resistive magnetohydrodynamics equations in a fully coupled form. The numerical method is based on the face‐centered unstructured finite volume approximation, where the velocity and magnetic field vector components are defined at the center of edges/faces; meanwhile, the pressure term is defined at element centroid. In order to enforce a divergence‐free magnetic field, the gradient of a scalar Lagrange multiplier is introduced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…This approach can potentially achieve the desired accuracy for a multidisciplinary problem under consideration by requiring substantially more resources and expertise in developing and maintaining such specialized code [11]. A more recent work devoted to monolithic approaches can be seen in [15][16][17][18][19][20][21][22][23][24][25][26][27][28], and a comprehensive review of the recent developments of robust monolithic FSI solvers can be found in [29]. Among them, a monolithic approach in an Eulerian frame [23,27] works like the fully Eulerian formulation [13,30].…”
Section: Introductionmentioning
confidence: 99%
“…This approach can potentially achieve the desired accuracy for a multidisciplinary problem under consideration by requiring substantially more resources and expertise in developing and maintaining such specialized code [11]. A more recent work devoted to monolithic approaches can be seen in [15][16][17][18][19][20][21][22][23][24][25][26][27][28], and a comprehensive review of the recent developments of robust monolithic FSI solvers can be found in [29]. Among them, a monolithic approach in an Eulerian frame [23,27] works like the fully Eulerian formulation [13,30].…”
Section: Introductionmentioning
confidence: 99%